The Impact of Money Politics on Democracy - Moonti, Roy Marthen; bunga, Marten (Law Research Review Quarterly, 2018)
Money politic, being recognized or not, is a very frightening scourge for democratic process in Indonesia. Politic and money are two different things but cannot be separated each other. It is because by doing politic, people need money, and with money, people can do the politic. The politic, basically, is a very tantalize arena to do various transactions which is well-known as money politic. The money politic is not a new thing for democratic system in Indonesia. From the very first time direct election is carried out, the money politic practices have been done, thus, we must be aware to those practices. We must not involve in money politic practices, because it is clearly harm the democratic process of this nation. Besides, the money politic not only underestimates the electors and the politicians, but also the democratic institution of this nation. Therefore, it causes some continuously conflicts which basically damages the national stability. The conflicts caused by money politic are unstable politic climate and situation, reducing the opportunity for the qualified district heads, influencing the people’s politic participation in both district head and general elections and harming the democratic as well as people.